The association of screen time and the risk of sleep outcomes: a systematic review and meta-analysis - He, Xin; Pan, Bei; Ma, Ning; Li, Dan; Kong, Weize; Liu, Qian; Liu, Xiaowei; Wang, Xiaoman; Deng, Xiyuan; Yang, Kehu (Frontiers in Psychiatry, 2025)
IntroductionScreen time has become increasingly prevalent in modern life and may influence various health outcomes, including sleep patterns. Previous meta-analyses examining the relationship between screen time and sleep have been limited by incomplete population coverage and insufficient consideration of potential effect modifiers. To address these gaps, we conducted a comprehensive meta-analysis to investigate the association between screen time and sleep outcomes across diverse populations.MethodsTwo independent reviewers screened studies and extracted data following a pre-registered protocol. Standardized coefficients (β) and odds ratios (OR) were used to quantify effect sizes. Random-effects meta-analyses were conducted using STATA 17.0, with subgroup analyses performed to explore effect modifiers.ResultsWe included 21 cohort studies with 548,338 participants. Each additional hour of daily screen time was associated with approximately 3 to 5 minutes shorter total sleep duration (β = −0.05, 95% CI: −0.08 to −0.03) in 11 studies reporting continuous outcomes, and with a higher risk of short sleep in nine studies reporting binary outcomes (OR = 1.25, 95% CI, 1.08 to 1.40). Subgroup analyses found no significant effect modification by age, region, short sleep definition or follow-up duration (all P interaction > 0.05). However, for binary outcomes, the association between screen time and short sleep differed significantly across countries (P interaction = 0.004). For other sleep outcomes, longer screen time was associated with increased risk of insomnia symptoms (β = 0.41, 95% CI, 0.18 to 0.63), delayed bedtime (13.2 minutes delay per hour of screen time), and difficulty initiating sleep (OR = 3.05; 95%CI: 1.51 to 6.24).ConclusionThis systematic review demonstrates a robust association between increased screen time and adverse sleep outcomes, with adolescents showing particular vulnerability. These findings underscore the importance of screen time management in sleep health promotion and suggest the need for age-specific interventions. Future research should focus on establishing causal relationships and developing evidence-based guidelines for optimal screen use across different age groups.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023476130.